Terrestrial toxicity model for nickel: Comparison of culture method and modeling approaches. (26th February 2018) - Jiang, Yang; Zhao, Xiaopeng; Gu, Xueyuan; Gu, Cheng; Wang, Xiaorong
Abstract: In metal toxicity model studies of soil–plant systems, hydroponic culture is often employed to simulate soil conditions, but the validity of this approach has not been examined. The present study evaluated Ni toxicity to wheat root elongation using models developed in hydroponic and sand cultures and then compared the results with those obtained from real soils. Three mechanism toxicity models were examined: the free ion activity model, the biotic ligand model (BLM), and the Gouy‐Chapman‐Stern model. After being developed in hydroponic and sand culture bioassays, the models were validated with 18 soils from across China. The results showed that more accurate predictions were obtained with sand rather than hydroponic bioassays. Dissolved organic matter exerted only a limited effect on Ni toxicity, whereas an important role was found for osmotic effects. Of the 3 models, the sand‐based BLM best predicted Ni toxicity to wheat root elongation (root‐mean‐square error = 16.2% and R 2 = 0.79) and was as good as the BLM estimated directly from soils. The present study shows that sand is a better matrix than solution for root elongation bioassays of Ni toxicity and that osmotic effects must be taken into account in evaluating soil conditions. Environ Toxicol Chem 2018;37:1349–1358. © 2018 SETAC Abstract :